(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Elena Yu. Tretyakova (Krasnodar, Russian Federation) The article suggests that the study of individualized elements of style cannot exhaust the peculiarities of the creative style of such writers as A.I. Solzhenitsyn. Using the example of the literary-critical works of J. Niva and a number of scientific studies, it is shown that these, recognized as authoritative, interpretations do not take into account Solzhenitsyn’s epic dominant of creativity: the positivist toolkit does not contribute, but prevents the inclusion and understanding of the mechanisms of non-individualistic processing of the meaning in the language. In expressing his creative credo, A. I. Solzhenitsyn repeatedly emphasized his desire to be a Christian writer. Defending a commitment to culture-faith, he entered into irreconcilable conflict with the positivist dogma. His inherent non-individualistic sense of language was manifested both in “Little Hearts” and in epic works, in the “Russian Dictionary of Language Expansion”, and in the records about the works of favorite authors (“Literary Collection”) imbued with the desire to be extremely honest before their native culture. The author of the article proposes to intensify the development of philological tools, which make it possible to reveal the dominants of the linguistic personality of epic writers, which are directly caused by the nature of natural languages. The source of this methodology is in the writings of XIX century Russian Humboldtans. (I. V. Kireevsky, A. A. Potebnya, and others), whose linguophilosophical ideas and research methods can be reintroduced into scientific use and applied to explain epic phenomena. Key words: A.I. Solzhenitsyn, the writer’s linguistic personality, epic artistic consciousness, national language, nationality, culture-faith, Russian Humboldtism. DOI 10.23683/1995-0640-2019-3-61-68